Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-03-23T15:18:38+01:00
Salut,

Premièrement, tu sais que a² - b² = (a+b)(a-b)

Ici, 4x² - 9/4 = (2x)² - (3/2)² = (2x - 3/2)(2x+3/2)

Tu sais qu'un produit de facteurs est nul si et seulement si un des termes est nul:

(2x - 3/2)(2x+3/2) = 0
2x - 3/2 = 0
2x = 3/2
x = (3/2) / 2 =  3/4

2x + 3/2 = 0
2x = -3/2
x = (-3/2) / 2 = -3/4

Bonne journée !

2014-03-23T15:21:21+01:00
4x²-9/4 = 0   avec 4=2² et 9=3²
(2x)² - (3/2)² = 0 
(2x+3/2)(2x-3/2)=0
2x+3/2=0 ou 2x-3/2 = 0
2x = -3/2 ou 2x = 3/2
x=-3/4 ou x=3/4